Human exposure to radon radiation geohazard in Rong Cave, Dong Van Karst Plateau Geopark, Vietnam - Nguyet, Nguyen Thi Anh; Duong, Nguyen Thuy; Schimmelmann, Arndt; Huong, Nguyen Van (Vietnam Journal of Earth Sciences, 2018)
Rong Cave is one of the more important caves in northern Vietnam’s Dong Van Karst Plateau Geopark (part of the Global Geoparks Network), because its subterranean lake provides agricultural and domestic water for neighboring communities. Maintenance and utilization of Rong Cave’s water reservoir, as well as touristic cave use, require frequent human access to Rong Cave. Depending on the availability of seasonal drip water and the water level of the lake, the abundant clay-rich sediment in the back portion of Rong Cave and possible seepage of gas from deeper strata along geologic faults provide seasonally elevated concentrations of radon in cave air. Based on repeated measurements over 10 months in 2015 and 2016 of the concentrations of radon isotopes (222Rn and 220Rn, also called thoron) with a portable SARAD® RTM 2200 instrument (SARAD® GmbH, Germany), the human total annual inhalation dose was estimated according to the UNSCEAR (2000) algorithm. The result indicates that the radon-related radiation exposure is insignificant for short-term visitors but may reach ~1.8 mSv a-1 for tour guides and ~25 mSv a-1 for cave utility workers. The latter values exceed the IAEA-recommended safety threshold of 1 mSv a-1 (IAEA, 1996). We recommend radiation monitoring for cave utility workers and tour guides.  Prolonged human presence in Rong Cave should be avoided during periods of seasonally elevated radon concentrations.References Cigna A.A., 2005. Radon in caves. Interna-tional Journal of Speleology 34(1-2), 1-18. Ha Giang Statistics Office (GSO), 2016. Statistical Yearbook of Ha Giang 2015, 404 pages, Ha Giang (in Vietnamese). Dumitru O.A., Onac B.P., Fornós J.J., Cosma C., Ginés A., Ginés J., Merino A., 2015. Radon survey in caves from Mallorca Island, Spain. Science of The Total Environment, 526, 196-203. Etiope G., Martinelli G., 2002. Migration of carrier and trace gases in the geosphere: An overview. Physics of the Earth and Planetary Interiors, 129(3-4), 185-204. Global Geoparks Network (GGN), 2010. Dong Van Karst Plateau Geopark. http://www.globalgeopark.org/aboutggn/list/vietnam/6509.htm Gregorič A., Vaupotič J., Šebela S., 2013. The role of cave ventilation in governing cave air temperature and radon levels (Postojna Cave, Slovenia). International Journal of Climatology 34, 1488-1500. Gunn J., 2003. Radon in caves. In Gunn J (Ed.): Encyclopedia of Caves and Karst Science. Fitzroy Dearborn (Taylor & Francis Books, Inc.), London, UK, 617-619. International Atomic Energy Agency (IAEA), 1996. Quality assurance for safety in nuclear power plants and other nuclear installations. Safety standards and guides, In: Safety series Q1-Q14. A publication within the Nuss programme. International Commission on Radiological Protection (ICRP), 2003. Database of Dose Coefficients: Workers and Members of the Public, Version 2.0.1 (CD- ROM), Elsevier Science, Amsterdam. International Commission on Radiological Protection (ICRP), 2010. Lung cancer risk from radon and progeny and Statement of radon. ICPR Pub. 115. Ann. ICPR 40(1). Markkanen M., Arvela H., 1992. Radon emanation from soils. Radiation Protection Dosimetry, 45(1-4), 269-272. Meisenberg O., Mishra R., Joshi M., Gierl S., Rout R., Guo L., Agaarwwal T., Kanse S., Irlinger J., Sapra B.K., Tschiersch J., 2017. Radon and thoron inhalation doses in dwellings with earthen architecture: Comparison of measurement methods. Science of The Total Environment, 579, 1855-1862. Morawska L., Phillips C.R., 1993. Depend-ence of the radon emanation coefficient on radium distribution and internal structure of the material, Geochimica et Cosmochimica Acta, 57(8), 1783-1797. Nguyen Thuy Duong, Nguyen Van Huong, Arndt Schimmelmann, Nguyen Thi Anh Nguyet, Dang Thi Phuong Thao, Ta Hoa Phuong, 2016. Radon concentrations in karst caves in Dong Van karst plat-eau. VNU Journal of Science - Earth and Environmental Sciences, 32(2S), 187-197 (in Vietnamese). Nguyen Thuy Duong, Arndt Schimmelmann, Nguyen Van Huong, Agnieszka Drobniak, Jay T. Lennon, Ta Hoa Phuong, Nguyen Thi Anh Nguyet, 2017. Subterranean microbial oxidation of atmospheric methane in cavernous tropical karst. Chemical Ge-ology, 466, 229-238. Nguyen Van Huong, Nguyen Thuy Duong, Nguyen Thi Anh Nguyet, Pham Nu Quynh Nhi, Dang Thi Phuong Thao, Tran Van Phong, Nguyen Ngoc Anh, 2016. Cenozoic tectonics in Dong Van karst plateau recorded in karst cave system. VNU Journal of Science - Earth and Environmental Sciences, 32(2S), 45-58 (in Vietnamese). Nguyen Anh Nguyet, Nguyen Thuy Dương, Arndt Schimmelmann, Nguyen Van Hu-ong, Ta Hoa Phuong, Dang Phuong Thao, Ma Ngoc Giang, 2016. Radon concentration in Rong cave in Dong Van Karst Plateau Geopark. Proceeding of International Symposium Hanoi Geoengineering 2016, 248-253. The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR), 1993. Report to the General Assembly, with scientific annexes. United Nations sales publication E.94.IX.2. United Nations, New York. The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR), 2000. UNSCEAR 2000 Report. In: Sources, vol. I. United Nations, New York. The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR), 2008. UNSCEAR 2000 Report. In: Sources, vol. I. United Nations, New York. Vietnamese Standards (TCVN 7889:2008), 2008. Natural Radon activity in buildings-Levels and general requirements of measuring methods, Ministry of Science and Technology and Ministry of Construction (Viet Nam) (in Vietnamese). Tong-Dzuy Thanh, Vu Khuc (Eds), 2011. Stratigraphic units of Vietnam. Vietnam National University Publisher, 553p. Walia V., Lin S.J., Fu C.C., Yang T.F., Hong W.L., Wen K.L., Chen C.H., 2010. Soil-gas monitoring: A tool for fault delineation studies along Hsinhua Fault (Tainan), Southern Taiwan. Applied Geochemistry, 25(4), 602-607. Wang J., Meisenberg O., Chen Y., Karg E., Tschiersch J., 2011. Mitigation of radon and thoron decay products by filtration. Science of The Total Environment, 409(19), 3613-3619. World Health Organization (WHO), 2000. Air Quality Guidelines for Europe, (2nd edition). WHO Regional Publications, European Series, 91, Chapter 8.3 - Radon.